500 juvenile recidivists (Archives of Criminology, 1960)
The research conducted by the Department of criminology of the Institute of Legal sciences has covered 240 juvenile recidivists in Warsaw, and 260 juvenile recidivists in Łodź, Katowice, Cracow and Białystok.In a total of 500 juvenile recidivists there were 463 boys and 37 girls. The age of the juveniles covered by the investigation was as follows: 116 recidivists were between 7 and 12 years of age, while 384 were between 13 and 16.The research carried out in Warsaw in the years 1954 to 1955 consisted in examining judicial records, in environment interviews, interviews at school, at the place of work, as well as in psychological and medical examinations. All the cases of recidivism, whether formal or actual, which came before the juvenile court, were included in the research. Follow-up studies, carried out several times, have made it possible to establish what were the further destinies of the juvenile recidivists after the lapse of some three years from the termination of the research.The research carried out in the four provincial juvenile courts was less detailed and did not comprise psychological or medical examination. Moreover, they could not be supplemented with follow-up studies. All the cases of juvenile recidivists which came before the juvenile courts in six months of the year 1954 were included in the research.The results of the follow-up studies in Warsaw are the following:It appeared that out of the 240 juvenile recidivists examined 116 continued to commit criminal offences within the following three years, 32 of them did not, to be sure, commit offences, but they could be considered as but partly reformed considering their unsettled way of life, their unsystematic work and the whole of their social attitude, while 54 had completely mended their ways. The remaining 38 examined persons could not be included into any of the preceding groups, since part of them still remained in correctional institutions and concerning the rest of them reliable data were lacking. Thus out of 202 juvenile recidivists in Warsaw the percentage of those who continued to commit offences within a three-year period after the termination of our research amounted to 57 per cent, and, over and above that, a further 16 per cent could not be considered as truly reformed.1. Out of the 500 juveniles recidivists examined only 49 per cent have both parents living, 30 per cent are being brought up only under the care of solitary mothers, 16 per cent have a stepfather and mother, or else a stepmother and father, 3 per cent are brought up by a solitary father, and 2 per cent are orphans who remain under the care of relations.The percentage of factory workers among the fathers amounted to 65 per cent, 13 per cent of the fathers were unskilled manual workers, 10 per cent were clerical workers, 4 per cent were handicraftsmen, and 2 per cent farmers.32.3 per cent of the mothers did not have any trade and had never worked, 30 per cent were employed as workers, 2s per cent worked manually as cleaners, laundresses, while 9 per cent were clerical workers.In the families where both parents are alive both father and mother worked in 52 per cent of the cases, and the father only - in 48 per cent. In the families where the mother is solitary, as many as 90 per cent of the mothers work.The material situation in the families investigated was described as bad in 47 per cent of the families, middling in 36 per cent and good - in 17 per cent.Taking into consideration both the social outlook of the families and an evaluation of the total of educational factors at work in the family home, four categories of families have been singled out:Family Group A, the most negative, where we have to do, first and foremost, with a particularly intense alcoholism of the fathers, a complete neglect of the home by the parents, bad relations between the parents, a delinquency of the father, a bad attitude towards the child, a lack of care for the child and control over it, and similar factors. These are family environments of the lowest moral level, in which the habitual drunkenness of the fathers has led to a decay of family life. Of such families there were 101, i.e. 20.2 per cent.Family Group B includes the families which also deserve a negative evaluation, but the intensity of negative factors in them is less than in the Group A families. The alcoholism of the fathers is also a typical factor here, only it assumes slightly lesser proportions, while the mothers show more care for their home. A lack of protection of the child, bad educational methods, bad material conditions are present in these families too, just as they are in Group A. of such families there were 125, i.e. 25 per cent.Family Group C consists, first and foremost, of those families in which the children are usually brought up by a solitary mother (42.5 per cent of the cases), who cannot cope with all her duties, and in which the children are deprived of proper care and control. Moreover, in those families where there is a stepfather or stepmother, a very bad attitude to the child and very faulty educational methods have been found to exist. Of such families there were 162, i.e. 32.4 per cent.Family Group D is composed of the families described as ,,good home environment", in which investigators have failed to find any factors negative in the educational sense. Both the moral level of the parents, their mutual relations and the care of the child were beyond any obvious criticism. Of such families there were only 112, i.e. 22.4 per cent. It ought to be stressed, however, that on the basis of the investigation which has been carried out it was not possible to establish properly either the whole of the complicated factors which go to form the educational atmosphere of the home, or fully to elucidate the father's and mother's emotional attitude to their child. It is, therefore, probable, that a detailed analysis of such good family environments (Group D) could yet bring to light the sources of such psychical experiences and emotional conflicts with the children under investigation, as did influence them, causing character deviations.In analyzing how, apart from the delinquency factor, data concerning the degree of demoralization of the five hundred juvenile recidivists investigated looked in the several family groups, and making use of such factors only as the degree of neglecting school work, the amount of playing truant from school, the number of flights from home, strolling about the streets in the company of demoralized schoolmates, etc., on the basis of the Chi-square test a significant relationship has been stated to exist between the type of family environment and the intensity of the demoralization of the juveniles investigated.What is noteworthy, besides, is the fact that among the brothers and sisters of the investigated there were the following percentages of children above 10 years of age, showing symptoms of very serious demoralization: in Group A families - 90 per cent, in Group B families - 32 per cent, in Group C families - 30 per cent, and in Group D families - only 8 per cent.The data concerning the further destinies of 202 Warsaw juvenile recidivists after a lapse of three years also testify to the fact that there exists a significant relationship between the type of family environment and the recidivism or else improvement of the investigated in the future. Of the juveniles seriously demoralized and continuing to steal systematically only 15.2 per cent came from Group D homes, i.e. those with a good reputation, while among the juveniles who had completely mended their ways a mere 7.4 per cent came from the worst family environments (Group A). Among the investigated brought up in those worst family environments as many as 68.5 per cent continued to steal systematically after a lapse of three years, while among the investigated who belonged to Group D families only 26.6 per cent continued to show recidivism on a large scale.2. On the basis of the results of psychological and psychiatric examination it can be stated that 42 per cent of the Warsaw juvenile recidivists exhibited various pathological traits, while among those of the investigated who later on proved unreformed the percentage of juveniles with pathological traitsamounted to 53.4 per cent, among the partly reformed - to 40.6 per cent, and among the entirely reformed - to 18.5 per cent.The percentage of children with psychopahatic traits and of children with symptoms of neurosis together constituted 22 per cent of the total of those examined in Warsaw (42 cases).Of children with symptoms of a post-traumatic state there were 16, of sufferers from epilepsia - 7, with post-encephalitic disorders - 3.Mental deficiency (feeblemindedness) has been stated in g per cent of the cases.Even though the majority of the recidivists who continued to commit criminal offences in the period of the next three years exhibited pathological traits, yet 47 per cent of the recidivists, with whom no such traits were found, also committed offences. On the other hand, among the entirely reformed there were 18.5 per cent of such recidivists who also exhibited pathological traits. Although on the basis of the Chi-square test we find a significant relationship to exist between pathological traits and the lack or the presence of moral improvement, yet we ought not to forget the dependence between other factors and the lack of improvement, which has been established in the course of tests.3. All the 500 juvenile recidivists examined committed thefts, even those few (16 per cent) who were tried for various other offences, also committed thefts. Barely 8 per cent of the boys examined committed thefts individually, while a typical phenomenon are thefts committed by them in a group of juvenile accomplices. 68 per cent of the investigated acted in gangs of three or more.43 per cent of the juvenile recidivists (boys) began to steal between the 7th and the 10th  year of their lives, and 28 per cent between the 11th and 12th.There exists a significant relationship between the early starting of delinquent activities and recidivism later on. Out of the investigated with whom the first thefts took place between the 7th and the 10th year of their lives as many as 72.5 per cent continued to steal during the period of follow-up studies, while only 11.4 per cent reformed. Similarly, those recidivists who had begun stealing at the age of from 11 to 12 continued to steal systematically in 68.4 per cent of the cases. On the other hand, such recidivists with whom the first thefts took place only at the. age of 13 or 14, or even of 15or 16, later on figured in the entirely reformed groups in 44 per cent and 52 per cent respectively.There also exists a significant association between the length of the period of committing thefts and the further destinies of the investigated. Those juvenile recidivists who had previously been stealing for from 3 to 4 years and from 5 to 9 years, later on figured in the ,,unreformed" group to the amount of 69 per cent and 63.5 per cent respectively. On the other hand, those juveniles with whom the period of committing thefts did not exceed two years formed almost equal percentages in the unreformed groups (52 per cent and 48 per cent respectively).The results of the investigation seem to speak in favor of the view that the younger the age of the juvenile delinquent, and the longer the period of his criminal activities, the bigger the probability that he will continue to commit thefts for at least several years to come. Moreover, those juvenile offenders who had started stealing at the age of from 7 to 10 years continued to steal then systematically in 85 per cent of the cases, while those juveniles who had started stealing only after completing their 13th or 14th year of age, later on stole only sporadically, at least in an overwhelming majority of the cases.Moreover, there exists a significant relationship between the systematic character of committing thefts and the lack of improvement later on. Out of the juvenile recidivists who stole ,systematically only 14 per cent were found, after the lapse of three years, in the entirely reformed group, while among those who stole only sporadically the percentage amounted to as many as 47 per cent.4. The majority of the juvenile recidivists stole, first and foremost, money, and, apart from money, food articles and single articles of clothing. OnIy 11 per cent of the investigated went in for stealing objects of greater value, such as watches, bicycles, etc. A typical theft concerned but a small numberof objects and the damage thereby caused was, as a rule, negligible. The place where thefts are most frequently perpetrated are shops and kiosks, and only after them - the family home and the school. Depending on the age of the investigated and on various lengths of the periods during which they committed offences there are, of course, differences, both as to the objects of theft and as to the places where the latter were committed.The thefts committed by the 37 recidivist girls investigated differed from the thefts committed by the boys. The girls stole almost exclusively money and articles of clothing, and it was only in exceptional cases that they committed thefts in shops. Girls began stealing a great deal later in Iife than the boys, and, as a rule, stole alone, without partners.The last chapter of the contribution discusses critically the practice of juvenile courts 'concerning the fight against the recidivism of juvenile offenders and the activities of the probation officers and correctional institutions.